Swami and his friends at the Malgudi post office - Raghuram, G., active 1996, (SAGE Knowledge. Cases., 1996)
The case aims to teach students about the problems and pitfalls of modernisation and improving efficiency. The case sets out the problem of a fictional post office, with average wait times for different services. The student is then invited to work out whether the introduction of a new computer system will reduce waiting times.